Discrimination of Sri Lankan black teas using fluorescence spectroscopy and linear discriminant analysis. (1st February 2013) - Seetohul, L Nitin; Scott, Simon M; O'Hare, William T; Ali, Zulfiqur; Islam, Meez
Abstract Background The quality of teas is currently graded using trained tea tasters, whose evaluation can sometimes be subjective. In this study the simple fluorescence‐based technique of total luminescence spectroscopy (TLS) in conjunction with data classification using principal component analysis (PCA) was applied to discriminate between teas from 11 different Sri Lankan plantations. Solvent extraction of the tea samples was followed by TLS to record excitation–emission matrices in the excitation range 250–590 nm and emission range 300–700 nm. Results The application of PCA and linear discriminant analysis (LDA) allowed the successful classification of all 11 teas using only the first two principal components. LDA demonstrated how the technique was able to discriminate between all teas correctly with 100% classification. Conclusion Further development of this work could lead to a simple device that could be used by tea manufacturers instead of or alongside trained tea tasters to grade teas. © 2013 Society of Chemical Industry